NLRP3-Dependent Pyroptosis: A Candidate Therapeutic Target for Depression - Wan, Teng; Li, Xiaoyu; Fu, Mingyuan; Gao, Xiaoyu; Li, Peiling; Guo, Weiming (Frontiers in Cellular Neuroscience, 2022)
Depression, a major public health problem, imposes a significant economic burden on society. Recent studies have gradually unveiled the important role of neuroinflammation in the pathogenesis of depression. Pyroptosis, a programmed cell death mediated by Gasdermins, is also considered to be an inflammatory cell death with links to inflammation. Pyroptosis has emerged as an important pathological mechanism in several neurological diseases and has been found to be involved in several neuroinflammatory-related diseases. A variety of chemical agents and natural products have been found capable of exerting therapeutic effects by modulating pyroptosis. Studies have shown that depression is closely associated with pyroptosis and the induced neuroinflammation of relevant brain regions such as hippocampus, amygdala, prefrontal cortex neurons, etc, in which the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome plays a crucial role. This article provides a timely review of recent findings on activation and regulation of pyroptosis in relation to depression.